2015
DOI: 10.1111/bij.12719
|View full text |Cite
|
Sign up to set email alerts
|

Do functional demands associated with locomotor habitat, diet, and activity pattern drive skull shape evolution in musteloid carnivorans?

Abstract: A major goal of evolutionary studies is to better understand how complex morphologies are related to the different functions and behaviours in which they are involved. For example, during locomotion and hunting behaviour, the head and the eyes have to stay at an appropriate level in order to reliably judge distance as well as to provide postural information. The morphology and orientation of the orbits and cranial base will have an impact on eye orientation. Consequently, variation in orbital and cranial base … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
69
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 121 publications
3
69
1
1
Order By: Relevance
“…; Dumont et al. ), with subsequent within‐family ecomorphological adaptations (Mattson ; Sacco and Van Valkenburgh ; Figueirido et al. ; Jones and Goswami ; Slater et al.…”
Section: Discussionmentioning
confidence: 99%
“…; Dumont et al. ), with subsequent within‐family ecomorphological adaptations (Mattson ; Sacco and Van Valkenburgh ; Figueirido et al. ; Jones and Goswami ; Slater et al.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, evolutionary shifts towards relatively higher bite forces can also occur through modification of skull shape such as increasing the size of attachment sites of the jaw adductor muscles and/or enhancing mechanical advantage of jaw closure by lengthening the input levers of the jaw adductors and/or shortening the jaw length (Radinsky, ; Santana et al ., ; Collar et al ., ; Zelditch et al ., ). Many researchers have identified significant shape differences between species with different dietary ecologies (Dumont et al ., ; Zelditch et al ., ; McLean et al ., ), but few have examined whether these shape differences also translate to bite force differences. Although some clades exhibit strong correlations between size‐corrected bite force and cranial shapes (Herrel et al ., ; Nogueira et al ., ; Dollion et al ., ), the vast majority of vertebrate clades exhibit many‐to‐one mapping of form to function where distinct cranial morphologies lead to the same feeding performance (Alfaro et al ., ; Wainwright et al ., ; Young et al ., ; Collar et al ., ; Kolmann et al ., ; Zelditch et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…In a comparative study of 31 musteloid species, Dumont et al . () found that cranial shapes significantly differed between dietary ecologies. However, whether these differences in cranial shape translate to functional differences such as estimated bite force between dietary groups remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Musteloids (e.g., badgers, otters, raccoons, skunks, and weasels) are a speciose and ecologically diverse clade of carnivorans (Fabre et al 2013Dumont et al 2015;Law et al 2018). Musteloids (e.g., badgers, otters, raccoons, skunks, and weasels) are a speciose and ecologically diverse clade of carnivorans (Fabre et al 2013Dumont et al 2015;Law et al 2018).…”
mentioning
confidence: 99%